2006
DOI: 10.1055/s-2006-950421
|View full text |Cite
|
Sign up to set email alerts
|

Acids as Proline Co-catalysts in the Aldol Reaction of 1,3-Dioxan-5-ones

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Most reports only note the dr for stereoisomers I and II , presumably because the yields of III and IV are too small to quantify. Majewski was the first to demonstrate this concept through amine catalysis, [135] but it was Gong who examined more meaningful substrates that likely invigorated extensive further study [136] . Unfortunately, Gong's initial stereochemical assignment was incorrect, but he soon amended the assignment, through X‐ray structure procurement, to show the major product as stereoisomer I .…”
Section: Specific Ketones and Their Reaction With 4‐nitrobenzaldehyde...mentioning
confidence: 99%
“…Most reports only note the dr for stereoisomers I and II , presumably because the yields of III and IV are too small to quantify. Majewski was the first to demonstrate this concept through amine catalysis, [135] but it was Gong who examined more meaningful substrates that likely invigorated extensive further study [136] . Unfortunately, Gong's initial stereochemical assignment was incorrect, but he soon amended the assignment, through X‐ray structure procurement, to show the major product as stereoisomer I .…”
Section: Specific Ketones and Their Reaction With 4‐nitrobenzaldehyde...mentioning
confidence: 99%
“…Recently, kinetic and spectroscopic studies revealed that the addition of water increased the proline concentration because of the inhibition of the formation of parasitic species such as the oxazolidinone derivative decreasing the relative concentration of key iminium intermediates by Le Châtelier's principle [83]. Moreover, the addition of Brønsted/Lewis acids such as chiral camphorsulfonic acid (CSA) [84], pyridinium p-toluenesulfonate, or lithium chloride [85] or even the combination of water with acetic and trifluoroacetic acid (TFA) or bases, such as 1,8-diazabyciclo [5.4.0]undec-7-ene (DBU) or triethylamine, showed a benefit effect on the reaction rates [86]. Also, the use of chiral diols, such as (R)-BINOL, as cocatalyst improved the obtained results [87], where this effect is explained by the formation of a template from the chiral diol that may activate and order the aldehyde and enamine nucleophile.…”
Section: Aldehydes As Electrophilesmentioning
confidence: 99%
“…The synthesis of products 372 could be accomplished by using the reaction of the corresponding α-isothiocyanates derived from isatins with simple ketones in the presence of thiourea (375, 20 mol%) as catalyst in mesitylene at −40 • C (75-95% yield, 40-80% de, and 64-98% ee) [434]. α-Isothiocyanato imides 371 reacted also with α-keto esters (85) to form β-hydroxy-α-amino acid derivatives in good results (70-99%, 40-70% de, and 79-98% ee) and catalyzed by thiourea (376, 5 mol%) in methyl tert-butyl ether at 25 • C [435].…”
Section: Ketones As Source Of Nucleophilementioning
confidence: 99%
“…As further confirmation, 2,2-dimethyl-1,3-dioxan-5-one 1c (Table 5) also displayed good reactivity and stereoselectivity when reacted with less reactive aldehydes 2g and 2d. In particular, our results represent the first examples of organocatalyzed aldol condensation between 2,2-dimethyl-1, 3-dioxan-5-one 1c and 4-Br benzaldehyde 2g or benzaldehyde 2d, promoted by only 10 mol% of proline [129][130][131][132][133].…”
Section: Application Of the Protocol To Other Ketonesmentioning
confidence: 68%